Quantum mechanics : the theoretical minimum - Susskind, Leonard; Friedman, Art. (London : Penguin Books, 2015)
Explains the theory and associated mathematics of quantum mechanics, discussing topics ranging from uncertainty and time dependence to particle and wave states.--
Systems and experiments -- Quantum states -- Principles of quantum mechanics -- Time and change -- Uncertainty and time dependence -- Combining systems : entanglement -- More on entanglement -- Particles and waves -- Particle dynamics -- The harmonic oscillator.
Includes index.
Keywords: Quantum theory -- Popular works; Computer science